Learning Leadership in Building a Culture of Information Technology in Elementary Schools - Sutapa, Mada; Syam, Aldo Redho; Arifin, Imron; Bafadal, Ibrahim; Burhanuddin (LETIGES, 2025)
This paper aims to describe learning leadership in building a culture of information technology and utilizing it to improve the quality of elementary school organizations based on digital developments in Indonesia. This article uses a qualitative approach with a multi-case study method. Data were obtained from key informants, elementary school documents and books, as well as journals and articles that support the research on learning leadership in building a culture of information technology in the digital era. The findings show that principal’s leadership plays a central role, not only by issuing policies but also by modeling, guiding teachers, and fostering collaboration that integrates technology into daily learning practices. This leadership focus transforms technology use into a sustainable school culture rather than a temporary response to the pandemic. The use of information technology is not only carried out in learning, but academic activities and school management have also begun to incorporate digital-based information technology. The learning leadership of school principals can be seen in their role in organizing the acculturation of information technology utilization through school policies and activity programs, especially in developing learning activities. Limitations include the fact that learning in the classroom is not fully digital-based, as elementary school learning still prioritizes face-to-face interactions between teachers and students. This study develops its setting and orientation by emphasizing leadership values in educational management. The study highlights the importance of the learning leadership of school principals in developing learning innovations at their schools, especially in the development of a digital-based information technology culture.